Vad gör egentligen en landskapsarkitekt? - Köppen Liljeblad, Ida (2009)

(untitled)
This is a thesis written at the Swedish University of Agriculture in Alnarp within the landscape architecture education. The essay deals with the landscape architect's professional identity and how it is described in different contexts along with how it is perceived by professional landscape architects. Misunderstandings and preconceptions concerning the landscape architect's professional identity is common, both within and outside the branch of industry that includes the vocation. This raises problems within the industry and for the individual landscape architect. To find out if the root of the problems lies in available descriptions of the occupation a study has been made. The study includes how the landscape architect is defined in easily accessible information from the internet and in literature as well as in industry-oriented information such as dissertations and information from Sveriges Arkitekter (the Swedish Architects). Interviews with professional landscape architects created a comparative material to what is written. The written information was compared with the professional’s selfimage. The conclusion of the study is that the written information is quite similar to the image that the respondents landscape architects have of their profession. The problem is not primarily based in the image given in print but in the communication within the branch of industry. The type of information that has been studied could be developed to ease communication between landscape architects and the other professionals in the future.